Analysis Factors Related To The Incidence Of Diarrhea In Toddlers In The Uptd Area Of The East Martapura Health Center, Banjar Regency - Elisa Oktaviani Dewi Anggraeni; Husaini Husaini; Edi Hartoyo; Erida Wydiamala (Journal Of Social Science (JoSS), 2023)
Diarrhea is a disease that causes discharge of feces more than 3 times with a liquid consistency, which may be accompanied by blood or mucus, and the frequency is more frequent than normal (WHO, 2019). According to WHO and UNICEF, there are around 2 billion cases of diarrhea and 1.9 million children under five die from diarrhea worldwide every year. The 2018 Basic Health Research stated that the prevalence of diarrhea for all age groups was 8% and the prevalence rate for toddlers was 12.3%, while for infants, the prevalence of diarrhea was 10.6%. The aim of the study was to analyze the relationship between Hand Washing with Soap (CTPS), Latrine Ownership, Garbage Securing and Diarrhea in the UPTD of the East Martapura Health Center. The method used is Quantitative, the research was conducted using a Cross Sectional study design, with a total sample of 89. The instruments used were questionnaires and observation sheets. Dependent variable: Incidence of diarrhea in toddlers, independent variables: hand washing with soap, toilet ownership, and waste management. The results of the study showed that there was a relationship between washing hands with soap (p=0.000), toilet ownership (p=0.000) and the incidence of diarrhea in toddlers. There is no relationship between waste management (p=0.065) and the incidence of diarrhea in toddlers in East Martapura. The most influential variable on the incidence of diarrhea among toddlers in East Martapura was latrine ownership (p=0.000 Exp (B) = 10.496).